Rechtsphilosophie im Spiegel der Zeit Beiträge zum Rechtsdenken Gustav Radbruchs (1878-1949) - Neumann, Ulfrid (Mohr Siebeck, 2021)
In his essays, Ulfrid Neumann aims to show that Radbruch succeeds in bringing a critique of knowledge into accordance with a value orientation by means of a neo-Kantian understanding of the value orientation of the law and by means of a comparison of the theoretical and practical philosophies. At no point in Radbruchs legal thought can he be simply consigned either to legal positivism or to a natural law position.
PublicationDate: 20210531
Keywords: Naturrecht -- Rechtspositivismus -- Radbruchsche Formel -- UN-Unrecht -- Rechtsphilosophie -- Rechtstheorie